Pembangunan E-Commerce Pada Kegiatan Penjualan Probiotik Herbal Sari Rempah Berbasis Website Study Kasus UKM “Wiro Djoyo” Reksosari - Khoirul Umam; Saiful Bahri; Donna Setiawati (JITU : Journal Informatic Technology And Communication, 2020)
The study is entitled the use of E-commerce to support MSMEs in marketing the "Wiro Djoyo" Case Study. UKM Wiro Djoyo Is one of the small and medium businesses engaged in selling herbal probiotics from Semarang such as herbal probiotics, tough and oil. This business is addressed to Reksosari, RT 09 / RW 01, Reksosari, Suruh, Semarang Regency. The product marketing system at Wiro Djoyo UKM is still very simple, namely by verbally conveying it by several people who have family ties or friends working with UKM Wiro Djoyo. Whereas for marketing the buyer still has to come to UKM Wiro Djoyo. So consumers who are far outside the area do not know the available address, so they are reluctant to come directly. The purpose of this study is to design, implement, and test e-commerce web-based e-commerce applications for product marketing at Wiro Djoyo. The research method used is a waterfall. Object modeling using UML. For coding using PHP and for databases using Myql. The results achieved are an e-commerce web to facilitate promotion and facilitate consumers in product marketing.